ANALISIS POTENSI RASIO CAMEL SEBAGAI INDIKATOR SINYAL KONDISI BERMASALAH BANK PERKREDITAN RAKYAT KONVENSIONAL DAERAH ISTIMEWA YOGYAKARTA - Gendro Wiyono (Jurnal Akuntansi, 2013)
The study was conducted to determine the potential of camel ratio as an indicator of signal problematic conditions of Conventional Rural Bank in Yogyakarta Special Region. The data used are all the Performance Rural Banks operating in 4 (four) districts and 1 (one) city of Yogyakarta, which is listed on the Bank of Indonesia. Due dependent variable is nominal data, then test of hypothesis is done using logit regression analysis model. The results provide evidence that: Adequacy Capital Ratio (Zstatistics = -5.4477; sig. = 0.0000) as a proxy for capital potentially significant factor as an indicator of signal problematic conditions; Non Performance Loan (Z Statistics = 6.3545; sig. = 0.0000) and Depreciation Reserve of Productive Assets (Z Statistics = 3.6966; sig. = 0.0002) as a proxy for asset quality factor potentially significant as an indicator of signal problematic conditions; Profit Margin (z Statistics = -1.3183; Sig. = 0.1874) as a proxy for management factor and Return On Assets (z Statistics = 0.1402; sig. = 0, 8884) as a proxy for earnings factor is not significant as an indicator of potentially problematic conditions signal; and Loan to Deposit Ratio (z Statistics = - 4.3700; sig. = 0.0000) as a proxy for liquidity potentially significant factor as an indicator of signal problematic conditions.